The Leadership Style of Muhammadiyah Elementary School Headmasters - Aji Heru Muslim; Sri Harmianto (Universitas Muhammadiyah Purwokerto, 2020)
This research aims to describe the headmaster’s leadership style at SD/MI (Primary School) Muhammadiyah in Banyumas Regency. This is a descriptive qualitative research. Subjects in this research are headmasters and teachers at SD/MI Muhammadiyah in Banyumas Regency, namely MI Muhammadiyah Wangon, SD Muhammadiyah Cipete, and MI Muhammadiyah Pasirmuncang. Data collection technique used in this research is interview. Data validity is checked using technique of source triangulation. The findings show that the leadership style implemented by headmasters at SD/MI Muhammadiyah in Banyumas Regency is a democratic leadership style. This is shown in the way the headmasters carry out their leadership function. For example, as a leader, the headmaster gives information, evaluation, motivation, and innovation for school development, runs situational and non-authoritarian leadership, behaves wisely, and gives directions, examples, as well as rewards. The headmaster always prioritizes a sense of unity and togetherness with the school community. The headmaster uses a strategy of getting close to the community. In dealing with problems, the headmaster solves them calmly and gracefully and discusses them in deliberations in accordance with the development of the problem, and after the decision the problem can be resolved properly. Moreover, the school principal is open to accepting opinions, criticisms and suggestions from staffs.